Environmental Management Accounting through the Lenses of Stakeholder, Institutional, and Legitimacy Theories: Implications with Environmental and Financial Performance in Albanian Companies - Sulanjaku, Marsel; Shingjergji, Ali (International Review of Management and Marketing, 2026)
The present study investigates the implementation and implications of Environmental Management Accounting (EMA) in Albanian companies’ environmental performance (EP) and financial performance (FP) through the perspectives of stakeholder, institutional and legitimacy theories. The research further, explores the impact of environmental performance on financial performance (EP). This study tested the proposed hypotheses in the research model utilizing the data collected from 287 participants, accountants and senior officers employed in companies across various industries in Albania. Structural Equation Modeling (SEM) was utilized to assess the collected data and to examine the relationships between the constructs. The findings of this study validate the direct and positive relationship between environmental management accounting (EMA) with both environmental performance (EP) and financial performance (EP) considered separately. Moreover, the empirical analysis confirmed that EP positively contributes to the enhancement of FP among Albanian companies. The empirical findings underscore the strategic importance of EMA implementation in emerging economies where environmental and financial objectives are often perceived as conflicting rather than complementary.